(x-3) *squared* + (y + 2) *squared* = 6
f(4)=9*4-2 =34 & g(4)= -2*4 =-8 then,
f(4)- g(4) = 34+8= 42
Answer:
$95777.5
Step-by-step explanation:
change 7% to decimal = .07
91,000 * .07 = 5370 (annual interest)
5370 / 12 = 530.83 (monthly interest)
530.83 * 9 = 4777.5 (9 months interest)
91,000 + 4777.5 = 95777.5 (initial + 9 months interest)
Answer:
9) u= -12
11) -18 over 2
Step-by-step explanation:
Hope this helps!!
Which statements are true about the ordered pair <span>(−1, 5)</span> and the system of equations?
<span>{<span><span>x+y=4 </span><span>x−y=−6</span></span></span>
Select each correct answer.
<span>The ordered pair <span>(−1, 5)</span> is a solution to the first equation because it makes the first equation true.The ordered pair <span>(−1, 5)</span> is a solution to the second equation because it makes the second equation true.The ordered pair <span>(−1, 5)</span> is not a solution to the system because it makes at least one of the equations false.The ordered pair <span>(−1, 5)</span> is a solution to the system because it makes both </span>